Web-Based Integrated Information System Model and User Behavior Analytics to Support Student Career Development and the Campus Entrepreneurship Ecosystem - Jayaun (Jurnal Ragam Pengabdian, 2026)
The rapid digital transformation in higher education has increased the demand for integrated information systems that not only support academic services but also facilitate student career development and campus entrepreneurship ecosystems. However, many universities still manage academic portals, career services, and entrepreneurship programs through separate systems, resulting in fragmented data, duplicated processes, and limited personalization of services for students. This condition prevents the optimal integration of academic performance, career interests, and entrepreneurial potential within a unified digital campus environment. This study aims to develop a conceptual model of a web-based integrated information system that leverages user behavior analytics to support student career development and strengthen campus entrepreneurship ecosystems. The research adopts a qualitative conceptual approach using a literature review method. A total of 15 relevant national and international publications related to higher education information systems, digital career platforms, campus entrepreneurship, web analytics, microservices architecture, and the PIECES evaluation framework were systematically analyzed. Data analysis was conducted through content analysis and conceptual synthesis to formulate the proposed system model. The results present a conceptual design of an integrated web-based information system consisting of academic, career development, entrepreneurship, and user behavior analytics modules within a unified architecture. The model is complemented by an evaluation framework that integrates the PIECES method with web analytics to assess system performance, information quality, efficiency, control, and service effectiveness. This study contributes a data-driven and adaptive conceptual model that can serve as a reference for universities in developing integrated digital systems oriented toward student needs, career readiness, and sustainable campus entrepreneurship development